The Effectiveness of Digital Storytelling in Developing Some English Language Communication Skills for Second Graders at Middle Schools in Jeddah - Altowairqi, Ghadah Abdulrahman Abdullah (Journal of Educational and Psychological Sciences, 2020)
The study aimed to measure the effectiveness of digital storytelling in providing second intermediate school students in Jeddah with communication skills in English language. The researcher used the quasi- experimental approach. A digital storytelling was designed and prepared in addition to the list of communication skills in English language. An achievement test was prepared، along with a performance test with an assessment card. The research sample consisted of (50) student from second intermediate school in Jeddah. They were randomly divided into two groups: the controlled group consisted of (25) students studying the educational content by digital storytelling، and the second one، the experimental group consisted of (25) students studying the educational content by traditional way. The research reached the following findings: There are statistically significant differences at (a=0.05) between the average scores of the experimental group using the digital storytelling and the average scores of the controlled one using the traditional way in the post- measurement of the achievement test along with the performance test and the assessment card in the listening skills in favor of the experimental group. There are statistically significant differences at (a=0.05) between the average scores of the experimental group using the digital storytelling and the average scores of the controlled one using the traditional way in the post- measurement of the achievement test along with the performance test and the assessment card in the speaking skills in favor of the experimental group. There are statistically significant differences at (a=0.05) between the average scores of the experimental group using the digital storytelling and the average scores of the controlled one using the traditional way in the post- measurement of the achievement test along with the performance test and the assessment card in the communication skills in favor of the experimental group. In light of such findings، the researcher recommends the following: Using the digital storytelling in providing both teachers and students with language skills, Training the teacher on how to produce digital storytelling and use them in the educational process to keep pace with the technological developments of this age.